Trade Liberalization and 'Export Response': Whither Complementary Reforms? - Correa, Paulo (2012)
What enables Ecuadorian manufacturing firms to start exporting? And what are the determinants of the share of total sales exported by a firm, once the decision of becoming an exporter has been made? We apply a Heckman selection model to the Ecuador's Investment Climate Survey (ICS) to investigate supply-side constraints to export performance at the firm level. We estimate export propensity (the probability of exporting) and export intensity (the share of total sales that are exported). The application of the Heckman selection model to a rich dataset as the ICS is a major contribution as previous applications of the Heckman selection model used much limited datasets, limiting the range of hypotheses to be tested. Furthermore, other studies on export performance based on ICS data use either Tobit or Probit models, incurring important methodological limitations. We find robust and stable relationships for export propensity and intensity with firm size, import of inputs, labor regulations, in-house R&D, quality certification, Web use, and foreign ownership. Capacity utilization and trade with the US positively affect export intensity, while trade within the Andean Community has the opposite effect in our outcome variable. No significant relationship was found with the infrastructure variables.